Echoes of the Posthuman in the Historical Development of Tibetan Folk Songs in Diqing, Yunnan Province - Wang, Shiying; Karin, Khomkrich; Boonsrianan, Pitsanu (Journal of Posthumanism, 2025)
This study investigates the historical development of Tibetan folk songs in Diqing Tibetan Autonomous Prefecture, Yunnan Province, through the lens of posthumanist theory. Set against the backdrop of cultural shifts from socialist institutionalization to digital globalization, the research explores how these folk songs have transformed in form, function, and meaning across three distinct periods: 1949–1979, 1979–2001, and 2001–2024. Drawing on ethnographic fieldwork conducted in Shangri-La County and surrounding villages between 2022 and 2024, the study incorporates interviews with five key cultural practitioners, archival analysis, and musicological transcription of 25 representative songs. Data were thematically coded and analyzed using narrative, stylistic, and technological frameworks. The results reveal that Tibetan folk songs have shifted from embodied, community-based practices to mediated cultural expressions shaped by state ideology, commercial tourism, and algorithmic curation. In the posthuman era, these songs are no longer solely authored by human agents; they participate in complex networks involving digital platforms, AI tools, and global audiences. The study contributes to contemporary posthumanist debates by rethinking cultural heritage as dynamic, relational, and multispecies. It suggests further research on how emerging technologies influence youth engagement with traditional music and calls for strategies that balance cultural preservation with creative innovation.